The role of the broadbed maker plough in Ethiopian farming systems: an ex post impact assessment study - Rutherford, A.S.; Odero, A.N.; Kruska, Russell L. (International Livestock Research Institute, 2001)
Five institutions including ILCA/ILRI, collaborated on the joint Vertisol Project (JVP) starting in 1986 for the sustainable use of Vertisol soils in Ethiopia. The improved soil drainage from the use of the broadbed maker (BBM) plough is one component of a technology package, that together with improved crop varieties, fertilisers and credit access can improve the well-being of farmers in Ethiopia by increasing grain and fodder yields. Several studies had been conducted previously in relation to the adoption of this technology. However, this ex post impact assessment was the first study undertaken since the research programme began and the BBM technology was developed for Ethiopia in 1986, to be focused on the impacts of the technology following adoption. The purpose of this study of the BBM is to assess quantitatively the returns to the research investment in this technology. The assessment was conducted using economic surplus methodology.